Research on LTE-WLAN Radio Interworking - Fang Xie; Nan Hu; Nan Li; Zhenping Hu; Guangyi Liu (Dianxin kexue, 2014)
Both LTE and WLAN are quite important networks for China Mobile in the near future. So it reserves to research on how to improve the cooperation efficiency and flexibility of these two networks, make full utilization of operator's resources, as well as offer better service for subscribers. First, existing LTE-WLAN cooperation mechanisms were discussed and the necessity of radio interworking method was analyzed.Then the radio interworking mechanisms and standardization progress were introduced. Finally some views on future work were proposed.